Model Pembelajaran Problem Based Learning dan Guided Discovery Learning Berbantu Media Pembelajaran Muvis Terhadap Literasi Sains - Aldi Yudawan; Bibin Rubini; Surti Kurniasih (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The research is aimed at finding out the difference of science literacy between the students of three classes with the learning models of Problem Based Learning (PBL) and Guided Discovery Learning (GDL) in the material of Life Organization using the media of Music and Video of Science (Muvis). It involved two classes: an experimental class and a control class. The population was students of SMPN 18 Bogor grade VII. The technique employed for taking the sample was Purposive Sampling. The sample used was the class of VII-A as the experimental class I. they were treated by Problem Based Learning (PBL) model and Muvis with the number of the students reached 35 students, the class of VII-B as the experimental class II was treated by Guided Discovery Learning (GDL) model and Muvis and the number of the students was 36 students. The last, the class of VII-C was made as the control class with no innovative treatment and they were 36 students. The test of ANAVA in the significant level of α = 0,05 showed that the value of Fobserved for science literacy was 52 and Ftable was 3,07, thus the value of Fobserved more than Ftable. Based on the result, the null hypothesis (H0) is rejected and the working hypothesis (H1) is accepted therefore, it can be concluded that there is difference of science literacy between PBL Muvis, GDL Muvis and the control class. The implementation of GDL Muvis in the class gave better influence to the science literacy compared to the implementation of PBL Muvis in another class and the control class with the average score of N-Gain 57.